Pengaruh Lokasi dan Kualitas Pelayanan Terhadap Minat Beli Ulang Konsumen - Yanti, Aprilah Dwi; Fathin, Afie Ammar; Anggara, Aziz Dwi (Jurnal Manajemen dan Bisnis (JMB), 2024)
This research aims to examine the influence of location and service quality on consumers' repurchase intentions. The study is conducted at the Ayam Geprek Mas Boy Pringsewu restaurant. It employs a quantitative approach with data collection through a questionnaire using a Likert scale that has been pre-tested for validity and reliability. The population for this research consists of consumers of Ayam Geprek Mas Boy Pringsewu. The sample size is 55 respondents, selected using the purposive sampling technique. The results of the study indicate that both location and service quality have a positive and significant impact on consumers' repurchase intentions.